POWER DISTRIBUTION LOG FEEDER (International Journal of Food and Nutritional Sciences, 2024)
Now-a-days, the field of Science and technology came up with incredible enhancements leading the human life to the advanced levels. The World now is in the position of doing wonders in the field of technologies. So, it is an innovation, which makes thewayofrecording of feeders information in a substation in a simple manner.Thisprojecthasbeenimplementedusing HTML, JAVASCRIPT, CSS,MySQLand PHP. The overall consumption of power across the feeder areas under particular substation. Apart from this, the project includes with attendance of men in the substation and profiles. The maintenance logbooks, load data and metering records in a substation are used in this project as a continuous effort to improve the use of digital format